Across The Boundaries Of Belief: Contemporary Issues In The Anthropology Of Religion - Klass, Morton (Taylor and Francis, 2018)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Introduction -- Part 1 Colonialism and Postcolonial Legacies -- 1 Anthropologists Versus Missionaries: The Influence of Presuppositions, Claude E. Stipe -- 2 From Tupa to the Land Without Evil: The Christianization of Tupi -Guarani Cosmology, -- 3 Shamanism and Christianity: Modern-Day Tlingit Elders Look at the Past, Sergei Kan -- 4 Reflections on Christianity in China, Morton H. Fried -- Part 2 Gender and Sexuality -- 5 Menstruation and Reproduction: An Oglala Case, -- 6 The Domestication of Religion: The Spiritual Guardianship of Elderly Jewish Women, Susan Sered -- 7 Becoming a Mujercita: Rituals, Fiestas, and Religious Discourses, Valentina Napolitano -- 8 Erotic Anthropology: "Ritualized Homosexuality" in Melanesia and Beyond, Deborah A. Elliston -- Part 3 The Healing Touch and Altered States -- 9 Exorcists, Psychiatrists, and the Problems of Possession in Northwest Madagascar, Lesley A. Sharp -- 10 The Woman Who Wanted To Be Her Father: A Case Analysis of Dybbuk Possession in a Hasidic Community, Yoram Bilu -- 11 Hypnosis and Trance Induction in the Surgeries of Brazilian Spiritist Healer-Mediums, Sidney M. Greenfield -- 12 Zar as Modernization in Contemporary Sudan, Susan M. Kenyon -- Part 4 Religion and the State -- 13 Pockets Full of Mistakes: The Personal Consequences of Religious Change in a Toraja Village, Douglas Hollan -- 14 Bandits, Beggars, and Ghosts: The Failure of State Control over Religious Interpretation in Taiwan, Robert P. Weller -- 15 Muslim Identity and Secularism in Contemporary Turkey: "The Headscarf Dispute -- " Emelie A. Olson -- 16 The Interpretation of Politics: A Hopi Conundrum, Peter M. Whiteley -- Part 5 Changes and Continuities -- 17 Cargoism in Irian Jaya Today, Benny Giay and fan A. Godschalk